What Factors are Associated with Health-Related Quality of Life in Mixed Dentition Children? - Luís Carlos Fantini; Diego Patrik Alves Carneiro; Giovana Cherubini Venezian; Carolina Carmo de Menezes; Silvia Amélia Scudeler Vedovello; Mario Vedovello Filho (Association of Support to Oral Health Research (APESB), 2022)
Objective: To associate the OHRQoL and HRQoL in mixed dentition children with the influence on age range, socioeconomic and clinical variables. Material and Methods: A cross-sectional study was carried out with 1,240 children between 6 and 12 years of age. HRQoL was assessed by the Quality of Life Assessment Scale, considered an outcome variable. OHRQoL was determined using specific questionnaires related to the age group: Oral Health Impact Scale in Early Childhood, Child Perceptions Questionnaire for 8 to 10 years, and 11 to 12 years. Dental caries and malocclusion were diagnosed. The socioeconomic class was evaluated. A multiple negative binomial regression analysis was used to test the relationship between HRQoL, OHRQoL scores and socioeconomic and clinical variables. Correlation analyses were performed between the total HRQoL and OHRQoL, with a significance level of 5%. Results: The HRQoL is inversely related to the impact of OHRQoL (p<0.05), modulated by the age group. There was a significant weak negative correlation between the HRQoL scores and the impact of OHRQoL (p<0.05). Conclusion:The OHRQoL impacts the HRQoL, modulated by the age group and with minor influence from socioeconomic and clinical variables.